The Clients’ Satisfaction of Health Care Servicesat Aselected Health Care Facility in Accra. (International Journal of Scientific Research and Management (IJSRM), 2017)
This study investigated the levels of satisfaction with healthcare among patients who visit a selected health care facility in Accra. A total of ninety-three respondents were sampled using the convenience sampling technique. Structured questionnaires developed by the researchers which examined the overall and specific satisfactions were administered to the respondents. The cross-sectional survey design was used for the study implementation. Data analysis was done using One-way ANOVA and Independent t-tests. The results showed that significant sex differences exist in the overall general and specific satisfaction between male and female customers. Significant age differences were also observed in the levels overall general and specific satisfactions. However, years of patronage did not have any significant effect on overall general and specific satisfactions. The implications of the study to healthcare delivery are extensively discussed.